4CPS-253 Differences between pharmaceutical interventions performed on antimicrobials in medical and surgical services. (22nd April 2022) - Fernandez, S; Ortonobes, S; Soler, N; Florit, M
Abstract : Background and importance: The increasing in-hospital use of antimicrobials requires pharmacists' involvement in multidisciplinary teams. Pharmaceutical interventions (PI) are essential to optimise antimicrobials' effectiveness and safety. Aim and objectives: To describe PI performed on antimicrobials in different hospitalisation services. To analyse differences between sociodemographic variables and mortality depending on type of service and PI performed. Material and methods: Retrospective observational study in a 750-bed university hospital. PI analysed from October 2020 to March 2021. Registered variables: PI type, service, age, length of stay (LOS) and mortality. Statistical analysis: Wilcoxon or Kruskal-Wallis test for quantitative variables; Chi-square test for qualitative variables. Results: Total PI performed: 16 913, 3145 (18.6%) on antimicrobials. PI at medical services 2449 (77.9%), surgical 696 (22.1%). Table 1 details the services with the most PI performed. Conclusion and relevance: The most common type of PI was administration/information, except in geriatrics where monitoring was predominant. Toxicity prevention is the second most frequent PI type in medical services; while effectiveness optimisation is second in surgical ones. LOS in surgical services is longer than medical services, with higher mortality in medical services. Patients with PI to prevent toxicity present higher mortality and, together with monitoring-requiring ones, are older. References and/or acknowledgements: Conflict of interest: No conflict of interest